2012
DOI: 10.1007/s11999-012-2400-x
|View full text |Cite
|
Sign up to set email alerts
|

Highly Crosslinked Polyethylene Does Not Reduce Aseptic Loosening in Cemented THA 10-year Findings of a Randomized Study

Abstract: Background Polyethylene (PE) wear particles are believed to cause aseptic loosening and thereby impair function in hip arthroplasty. Highly crosslinked polyethylene (XLPE) has low short-and medium-term wear rates. However, the longterm wear characteristics are unknown and it is unclear whether reduced wear particle burden improves function and survival of cemented hip arthroplasty. Questions/purposes We asked whether XLPE wear rates remain low up to 10 years and whether this leads to improved implant fixation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
59
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 43 publications
8
59
0
1
Order By: Relevance
“…Previous reports on this population with conventional polyethylene have been associated with unacceptably high component loosening and osteolysis [3,7,9,23,29,32,34,35]. Highly crosslinked polyethylene has had much less wear and osteolysis, even in the younger population [1,21,22,24,25]. Use of a counterface material such as ceramic or Oxinium to further decrease wear is also appealing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous reports on this population with conventional polyethylene have been associated with unacceptably high component loosening and osteolysis [3,7,9,23,29,32,34,35]. Highly crosslinked polyethylene has had much less wear and osteolysis, even in the younger population [1,21,22,24,25]. Use of a counterface material such as ceramic or Oxinium to further decrease wear is also appealing.…”
Section: Discussionmentioning
confidence: 99%
“…The low rate of HXLPE wear in our study is below the assumed wear threshold to produce particulate debris that is sufficient to cause osteolysis, assuming the particles are of comparable biologic activity and because of this, the survival should be equal to or improved when compared with conventional polyethylene. Two prospective randomized studies have demonstrated less wear but have not shown a reduction in aseptic loosening [17,21]. The studies include a relatively small number of patients (60, 54) randomized with one study reporting one failure of a cemented femur in the standard polyethylene group and two failures in the HXLPE group (p = 1.0) [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although contemporary THAs with highly crosslinked polyethylene (HXLPE) or hard-on-hard bearings offer great hope for reducing wear, the reduction in wear observed in THAs with HXLPE appears to be not quite as dramatic as seen in those with hard-on-hard bearings [19,32], and those with metal-on-metal bearings have problematic issues such as hypersensitivity and pseudotumors [34].…”
Section: Introductionmentioning
confidence: 99%